2017
DOI: 10.1007/s00162-017-0450-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective particle size from molecular dynamics simulations in fluids

Abstract: We report molecular dynamics simulations designed to investigate the effective size of colloidal particles suspended in a fluid in the vicinity of a rigid wall where all interactions are defined by smooth atomic potential functions. These simulations are used to assess how the behavior of this system at the atomistic length scale compares to continuum mechanics models. In order to determine the effective size of the particles, we calculate the solvent forces on spherical particles of different radii as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…1a. Because the pore sizes of most experimentally synthesized MOFs are in the range of 5-35 Å, 24,27 our pseudo nanoporous structures were built using different numbers of LJ spheres (n = 4, 7,10, 13,16,19,22,25,28,31,34,37,40) to create different predefined crystal cell lengths (l = 5, 12.5, 15, 17.5, 20, 22.5, 25, 27.5, 30, 32.5, 35 Å). The representative structures are presented in Fig.…”
Section: Porous Crystal Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a. Because the pore sizes of most experimentally synthesized MOFs are in the range of 5-35 Å, 24,27 our pseudo nanoporous structures were built using different numbers of LJ spheres (n = 4, 7,10, 13,16,19,22,25,28,31,34,37,40) to create different predefined crystal cell lengths (l = 5, 12.5, 15, 17.5, 20, 22.5, 25, 27.5, 30, 32.5, 35 Å). The representative structures are presented in Fig.…”
Section: Porous Crystal Constructionmentioning
confidence: 99%
“…36) with a nitrogen probe radius of 1.82 Å, in which the LJ parameter (σ) was used as van der Waals diameter of the framework atoms. [37][38][39] It was found that the accessible pore width for ethanol molecules should be greater than the dynamic size of ethanol molecules (3.95 Å) based on the TraPPE force field parameters of ethanol. GCMC simulations were carried out using RASPA 1.0 (ref.…”
Section: Gcmc Simulationsmentioning
confidence: 99%
“…Because of the repulsive interactions between the fluid particles and the colloidal particle, the radius of the colloidal particle is slightly larger than the packing radius. There have been discussions in the literature on determining the radius of a particle in MD simulations and the boundary conditions chosen for the calculation in eq . ,,,, In our study, we carried out bulk simulations with one colloidal particle in a fluid with PBCs in all three directions (no walls) to obtain the radial distribution function g ( r ) between the fluid particles and the COM of the colloidal particle as shown in Figure . The radius of the colloidal particle R was defined to be the largest distance without any fluid particles in the g ( r ).…”
Section: Calculation Detailsmentioning
confidence: 99%